2002
DOI: 10.1046/j.1471-4159.2002.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of a PDZ protein, SAP‐97, in the prefrontal cortex of patients with chronic schizophrenia

Abstract: Many postsynaptic density proteins carrying postsynaptic density-95/discs large/zone occludens-1 (PDZ) domain(s) interact with glutamate receptors to control receptor dynamics and synaptic plasticity. Here we examined the expression of PDZ proteins, synapse-associated protein (SAP) 97, postsynaptic density (PSD)-95, chapsyn-110, GRIP1 and SAP102, in post-mortem brains of schizophrenic patients and control subjects, and evaluated their contribution to schizophrenic pathology. Among these PDZ proteins, SAP97 exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 51 publications
7
75
0
Order By: Relevance
“…In our experiments, we found no changes in PSD95 expression, but decreased transcripts encoding NF-L in schizophrenia and SAP102 in BD. Previous studies have examined PSD95 expression in schizophrenia, and although a previous study found decreased transcript expression in DLPFC (Ohnuma et al, 2000), our results coincide with those that found no changes in PSD95 expression in the cerebral cortex by RT-PCR (Dracheva et al, 2005), immunoautoradiography (Toro and Deakin, 2005), and western blot analysis (Toyooka et al, 2002). Toyooka et al (2002) found decreased SAP102 protein expression in the hippocampus but not DLPFC in schizophrenia.…”
Section: Abnormalities Of Nmda-associated Proteins In Schizophrenia Asupporting
confidence: 89%
See 1 more Smart Citation
“…In our experiments, we found no changes in PSD95 expression, but decreased transcripts encoding NF-L in schizophrenia and SAP102 in BD. Previous studies have examined PSD95 expression in schizophrenia, and although a previous study found decreased transcript expression in DLPFC (Ohnuma et al, 2000), our results coincide with those that found no changes in PSD95 expression in the cerebral cortex by RT-PCR (Dracheva et al, 2005), immunoautoradiography (Toro and Deakin, 2005), and western blot analysis (Toyooka et al, 2002). Toyooka et al (2002) found decreased SAP102 protein expression in the hippocampus but not DLPFC in schizophrenia.…”
Section: Abnormalities Of Nmda-associated Proteins In Schizophrenia Asupporting
confidence: 89%
“…Previous studies have examined PSD95 expression in schizophrenia, and although a previous study found decreased transcript expression in DLPFC (Ohnuma et al, 2000), our results coincide with those that found no changes in PSD95 expression in the cerebral cortex by RT-PCR (Dracheva et al, 2005), immunoautoradiography (Toro and Deakin, 2005), and western blot analysis (Toyooka et al, 2002). Toyooka et al (2002) found decreased SAP102 protein expression in the hippocampus but not DLPFC in schizophrenia. Abnormal SAP102 expression in BD could affect the regulation of NMDA receptor exocytosis in the PSD, as SAP102 is a key protein in the exocyst complex that transports NMDA receptors from the ER to the postsynaptic membrane (Sans et al, 2003).…”
Section: Abnormalities Of Nmda-associated Proteins In Schizophrenia Asupporting
confidence: 89%
“…The decrease of synaptic NMDA receptor expression after haloperidol treatment is supported by the evidence that the expression of the scaffolding protein PSD95 is also reduced. To this end, a lower expression of NMDA receptor subunits and scaffolding proteins is also observed in prefrontal cortex of schizophrenics (Ohnuma et al, 2000;Toyooka et al, 2002;Kristiansen et al, 2006). Note that the diminished availability of active NMDA receptor is not observed in hippocampus, thus highlighting the regional selectivity of the changes brought about by haloperidol.…”
Section: Discussionmentioning
confidence: 86%
“…These scaffolds mediate insertion of the receptors into the membrane, and regulate receptor subunit composition at the cell surface (for overview see 70 ). Transcript analysis in postmortem schizophrenia and bipolar disorder brains has revealed decreased levels of SAP-97, SAP-102, and PSD 95 [24][25]135 . The gene DLG1, which encodes SAP-97, has been strongly linked to schizophrenia susceptibility 136 .…”
Section: Protein-scaffold Interactionsmentioning
confidence: 99%